Comparison Of The Effectiveness Of Akidah Akhlak Learning With The Geschool Platform And Google Classroom - Sutipyo Ru’iya; Yusron Masduki (At-Tarbiyat, 2022)
This study intends to describe the online learning process during the Covid-19 period at Madrasan Aliyah Negeri (MAN) "X" Sleman. This study also intends to compare the effectiveness of learning using the Google Meet platform with the Geschool platform. The research subjects included two moral creed teachers who used Google Meet with the Geschool platform. Data obtained by in-depth interviews, observation, and documentation. Data were analyzed using qualitative descriptive analysis. The results showed that MAN "X" Sleman made several innovations in learning to increase the effectiveness of learning. Implementation of learning innovations by providing effective learning training, which includes training on the use of learning platforms, making videos and conducting several workshops. Learning innovation is a combination of top-bottom and bottom-up models. The curriculum applied in learning is a curriculum in emergency conditions by prioritizing essential materials. The results also show that student learning using the Geschool platform is more effective than using the Google classroom platform, both in terms of student learning activities, task completion, and final results.